Inner satellites of Neptune: I the disturbing function - Yokoyama, T.; do Nascimento, C.; Santos, M. T. (Elsevier B.V., 2005)
In this work, we focus our attention to the expansion of the disturbing function (R) which governs the dynamics of a satellite (natural or artificial) in the Neptune-Triton system. What makes this problem quite unusual, is the fact that a small inner satellite can be strongly disturbed by Triton which is moving in a highly inclined and retrograde orbit. These features are unique in our solar system. Although a lot of retrograde satellites are currently known, all of them have negligible mass and the), do not offer almost any perturbation on the others satellites. However, in the case of the inner satellites of Neptune, Triton is an interesting exception. In a highly inclined orbit, the perturbation it exerts on the neighbouring satellites of Neptune cannot be ignored even for the present scenario. However, in the future, this perturbation will be much more important because due to the tides, the orbit of Triton is contracting, whereas the semi major axes of the remaining inner satellites of Neptune will remain almost unaffected by the tides. In this work we first obtain the disturbing function in the retrograde case. After that, we generalize R for arbitrary inclination. Several numerical tests are presented and a possible future case of resonant configuration is briefly discussed as well. (c) 2005 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: satellites of Neptune; Neptune-Triton system; disturbing function; retrograde orbit; dynamical astronomy